TEORETYCZNE PODŁOŻE KREACJI I REGULACJI EURO - Knakiewicz, Zenobia (Wydział Prawa i Administracji UAM, 2004)
The purpose of the article is to present the theoretical grounds for creating the common European currency, as well as its regulation and the method of rendering money supply. In the author’s opinion, the theoretical grounds comprise the views of K. Wicksell, J. M. Keynes and J. R. Hicks. On the basis of this hypothesis the nominal view of the currency was analysed, this view being considered as the source of the contemporary view of money in general. Also, the credit character of money was considered, the aspect being touched upon for the first time by K. Wicksell. The nature and characteristics of money were discussed in the views of J. R. Hicks and J. M. Keynes. Furthermore, a discussion was offered of the method of quantitative rendition of the euro supply in the EMU member states in addition to the method of affecting liquidity levels of banks comprising the ESCB and in consequence also the method of regulating the euro. The study was based upon the respective literature and the up- -to-date figures regarding the structure of money supply and positions determining the liquidity of national central banks within the EMU. Four tables were developed on the basis of original figures dated at the end of 2003 and the first quarter 2004. The data proved the hypothesis made by the author. An analysis of the data presented regarding the money supply in comparison with the so-called opposite positions and the data on the positions affecting liquidity levels of ESCB banks have all led to the conclusion that the contemporary money is debt, while long term deposits are not moneys but investment assets. It is necessary to regulate the creation of money. The constraint of the creation of non-cash money is the obligatory minimum reserves.
THEORETICAL GROUNDS FOR CREATING AND REGULATING THE EURO